On the page-number of a circulant graph - Xiaoyuan Dong; Dengju Ma (AKCE International Journal of Graphs and Combinatorics)
The page-number of a graph G, denoted by p(G), is the minimum k such that G has an embedding in a k-book. The circulant graph C(m, n) is such a graph that its vertex set is [Formula: see text] and edge set is [Formula: see text], where m, n are positive integers satisfying [Formula: see text] and indices is read modulo m. In the paper we show that the page-number of a circulant graph C(m, n) is three except for [Formula: see text], where the page-number of [Formula: see text] is two.